A novel thermal-mechanical model and the characteristics of interfacial stress in the laminated structure for flexible electronics. (17th November 2021) - Liu, Xu; Qiu, Yuanying; Wei, Yuan; Yan, Rui
Abstract: Flexible electronics have attracted rapidly growing interest owing to their great potential utility in numerous fundamental and emerging fields. However, there are urgent issues that remain as pending challenges in the interfacial stress and resulting failures of flexible electronics, especially for heterogeneous laminates of hard films adhered to soft polymer substrates under thermal and mechanical loads. This study focuses on the interfacial stress of a representative laminated structure, that is, the Si film is adhesively bonded to soft polydimethylsiloxane with a plastic polyethylene terephthalate substrate. An novel thermal-mechanical coupling model for this flexible structure is established in this paper, which presents the essential characteristics of interfacial shear stress. In addition, under thermal and mechanical loads, a typical case is investigated by combining an analytical solution with numerical results using the differential quadrature method. Furthermore, thermal and mechanical loads, material and geometry parameters are quantitatively explored for their influences on the interfacial shear stress. Targeted strategies for decreasing stress are also suggested. In conclusion, the thermal-mechanical model and application case analyses contribute to enhancing the design of interfacial reliability for flexible laminated structures.